Knee torque of an above-knee prosthesis for two-track alpine skiing - Demsar, I.; Duhovnik, J.; Supej, M. (Science and Skiing VII, 2018)
Alpine skiing is a hugely popular winter sport. In addition to non-disabled skiers, leg-amputee skiers make up a significant portion belongs (McCormick, 1984; O'Leary et a!., 1989). Types of skiing are differentiated according to the severity of amputation. People with a below-knee amputation of one leg can ski with or without an artificial limb (prosthesis) (Bowker and Michael, 1992). Most above-knee amputees ski on the intact leg only, using the three-track skiing technique (Jessen, 2012; McCormick, 1984). This technique involves skiing on the intact leg by using special poles (crutches) with skis fixed at the bottom. Skiing on both legs (the intact leg and the prosthetic leg) is used very rarely with above-knee amputees (DemSaret al., 2011). People with above-knee amputation of both legs can ski with the use of a short prostheses without a knee mechanism, or they can use a sit-ski or mono-ski (Cavacece et al., 2005, Gegenwarth & Reinelt, 2010). Compared to walking, leg kinematics and dynamics are substantially different in skiing. Sports activities such as alpine skiing require special types of artificial knee joints, allowing an accumulation of energy in the flexion phase and return of this energy in the extension phase (Krfill et al., 2010). According to currently available data, there are only two types of artificial knee joints available on the market that allow regular two-track skiing (XT9 ESPK, Symbiotechs, USA and ART-LEG Sport knee, Art-leg, Slovenia). The objective of this study was to analyze knee-joint dynamics during two-track alpine skiing of above-knee amputees and the impact of additional load on the torque in the prosthesis and the intact leg.